2018
DOI: 10.1186/s12885-018-4596-y
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of three lipid derivatives for postoperative gastric cancer mortality: the Fujian prospective investigation of cancer (FIESTA) study

Abstract: BackgroundAs we previously reported, the presence of preoperative metabolic syndrome can predict the significant risk of gastric cancer mortality. As a further extension, we evaluated the prediction of three lipid derivatives generated from triglycerides (TG), total cholesterol (TC), high- and low-density lipoprotein cholesterol (HDLC and LDLC) at baseline for postoperative gastric cancer mortality by prospectively analysing 3012 patients. The three lipid derivatives included the ratio of TC minus HDLC to HDLC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 41 publications
1
18
0
Order By: Relevance
“…TG and HDL-C are usually considered as the important serum lipids, which are involved in energy storage, signal transduction, and structural composition. Furthermore, several studies have reported that serum lipids were associated with clinical outcomes in many types of malignancies including GC 4, 14. The present study enrolled the training and test cohorts of GC patients to explore the correlation between serum lipids and GC.…”
Section: Discussionmentioning
confidence: 97%
“…TG and HDL-C are usually considered as the important serum lipids, which are involved in energy storage, signal transduction, and structural composition. Furthermore, several studies have reported that serum lipids were associated with clinical outcomes in many types of malignancies including GC 4, 14. The present study enrolled the training and test cohorts of GC patients to explore the correlation between serum lipids and GC.…”
Section: Discussionmentioning
confidence: 97%
“…A total of 6865 assessable patients were enrolled from Fujian Provincial Cancer Hospital (the current Fujian Cancer Hospital & Fujian Medical University Cancer Hospital) between January 2000 and December 2010, including 2535, 3012 and 1318 patients receiving radical surgery for esophageal cancer, gastric cancer and colorectal cancer, respectively, and all study patients were safely discharged and followed up until December 2015. Detailed information on study design, enrollment, eligibility criteria and follow-up evaluation has been described elsewhere 9-11,13-16.…”
Section: Methodsmentioning
confidence: 99%
“…If death occurred during follow-up, the exact date was traced either through his/her relatives or medical reports. The study design, recruitment procedure, eligibility criteria and follow-up assessment have been described previously 7-9,13,14,16.…”
Section: Methodsmentioning
confidence: 99%